Peran Pembiayaan Murabahah Dalam Pengembangan Kinerja Usaha Mikro Pada LKMS MM Sejahtera - Puja Syafitri; Jutian Desti; Raty Armalindasari (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This paper discusses the role of the MM Sejahtera Syariah Financial Institution through Murabahah financing in developing the performance of micro businesses and finds out what obstacles are faced by the MM Sejahtera Islamic Financial Institution and what are the supporting factors of the MM Sejahtera Islamic Financial Institution. The purpose of this study was to determine the extent to which the Islamic Financial Institution MM Sejahtera plays a role in developing the performance of micro businesses through murabahah financing, to find out what obstacles are faced and their solutions and to know the supporting factors in developing micro enterprises in MM Sejahtera Islamic Financial Instution. The research method is descriptive with a qualitative apporoach. Data collection techniques through interviews and field observations. Keywords : Financing, Islamic Microfinance Institutions, Business Performance